A mixture of p‐anisaldehyde and ethyl nicotinate elicits positive antennal and behavioral responses in Frankliniella occidentalis. Issue 7 (28th April 2022) - Tian, HouJun; Chen, YiXin; Chen, Yong; Chen, XiuQin; Lin, Shuo; Zhang, Jie; Yang, Guang; Wei, Hui
Abstract : Western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is a destructive, invasive pest that has spread rapidly throughout China. Traps for the prevention and control of thrips typically use a single attractant, and few studies have evaluated effective compound combinations. In this study, the attractant effects of ethyl nicotinate and p ‐anisaldehyde on female F. occidentalis were evaluated. Electroantennography recorded the highest depolarization for the mixture of p ‐anisaldehyde and ethyl nicotinate standards at a 1:1 mass ratio, and this depolarization was significantly higher than that of the other compounds investigated. The Y‐tube olfactometer results show that the olfactory responses of female F. occidentalis to ethyl nicotinate, p ‐anisaldehyde, and their mixtures (at a 1:1 mass ratio) at concentrations of 0.05, 0.1, 0.5, and 1 μg μl −1 were significantly higher than those to liquid paraffin. The strongest response was toward 0.05 g l −1 ethyl nicotinate or p ‐anisaldehyde and the 1 g l −1 mixture of p ‐anisaldehyde and ethyl nicotinate standards combined at a 1:1 mass ratio, but high concentration caused a weak reaction. Greenhouse experiments revealed that various concentrations of the attractants were successful in trapping thrips. The attractant mixture at a concentration of 1 g l −1 was the most effective at luring thrips. Compared with traps without any attractants, those with attractants trapped at least double the number of F. occidentalis . Our study is the first to comprehensively evaluate female F. occidentalis responses to p ‐anisaldehyde and ethyl nicotinate using electrophysiological, Y‐tube olfactometer, and greenhouse trapping analyses. The methods used also proved to be valuable for evaluating the potential of attractants to control F. occidentalis . Abstract : Insect‐trapping technology has emerged as an important means of ecological pest control, and complex attractants based on plant volatiles are at its core. Our study is the first to comprehensively evaluate female Frankliniella occidentalis (Thysanoptera: Thripidae) responses to p ‐anisaldehyde, ethyl nicotinate, and their mixture using electrophysiological, Y‐tube olfactometer, and greenhouse‐trapping analyses. Our experiments show that a mixture of ethyl nicotinate and p ‐anisaldehyde is an effective attractant for trapping thrips (1 g l −1 was the most effective concentration for luring female F. occidentalis ).